EFFECT FERTILIZER N, P DAN K ON SOME VARIETIES OF UPLAND RICE (Oryza sativa L.) FROM KUANTAN SINGINGI DISTRICT BEING PLANTED THE INCEPTISOL SOIL - Rina Fitri; Idwar '; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Rice plants (Oryza sativa L.) is important food crops in Indonesia to boost production of upland rice crop nutrients needed in sufficient quantities especially N, P dan K. This research aims is to determine where the rice varieties that give effect to N, P and K fertilizer. This research was conducted in screen house of Agriculture Faculty at Riau University, Pekanbaru. This research take 7 months start from August 2013 till February 2014. This research was performed experimentally using a Completely Randomized Design (CRD) consist of 2 factor, tested by LSD 5% level. The first factor is the upland rice varieties cosisting of varieties Santan, varieties Pulau Petai and vvarieties Inpago 5 and second factor N, P dan K fertilizer. The results showed the granting of a wide measure of fertilizer N, P dan K are not real movers shakers of all parameters, except for the amount of grain panicle effect is real and varieties pulau petai give relatively higher results when viewed from the result. Grating a rate of fertilizer (Urea 0,38 g, SP-36 0,34 g, KCl 0,15 g/clumps) on inpago varieties can increase the height of the plant, tillers maxsimum number, number of productive tillers and the amount of grain panicle. While granting a measure (Urea 0,75 g, SP-36 0,68 g, KCl 0,3 g/clumps) increased panicle emergence time, percentage pithy grain per panicle, grain weight clumps dan weight of 1000 filled grain. Keywords: fertilizer N, P and K, the local varieties of upland rice, yielding varieties.